Marketing death culture and the making of a life insurance market in China - Chan, Cheris Shun-ching. (New York ; Oxford : Oxford University Press, 2012)
Drawing on rich ethnographic data, this book documents the processes and politics through which local cultures shape the way a market is formed and thereby sheds light on the dynamics through which modern capitalist enterprises diffuse insurance to regions with different cultural traditions.
Description based on online resource; title from PDF title page (viewed on Apr. 26, 2012).
Includes bibliographical references.
Keywords: Life insurance -- Social aspects -- China